2019
DOI: 10.35940/ijeat.a1859.109119
|View full text |Cite
|
Sign up to set email alerts
|

IoT in Connected Cars: Challenges and Chances

Abstract: With pursuits to furnish secure and satisfied driving, various advanced driver assistance system (ADAS) has been developed over the preceding decades. They offer a broad range of offerings such as anti-lock braking systems (ABS), lane keeping assist (LKA), blind spot facts gadget (BLIS), cruise control (CC), adaptive cruise manage (ACC), etc. Modern vehicles are outfitted with part of sensors device like radar, ultrasonic, photography camera, light detection and ranging (LIDAR), etc., and Global Navigation Sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…In the category of Benefits and Challenges of V2V communication in smart traffic, studies have reported that V2V communication can improve road safety and traffic flow by providing timely and accurate information about the surrounding vehicles and the road environment [23], [24], allowing for more efficient and coordinated driving [22], [25]. Table 1 summarizes the benefits and challenges of V2V Communication in smart traffic systems.…”
Section: Results and Disccussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the category of Benefits and Challenges of V2V communication in smart traffic, studies have reported that V2V communication can improve road safety and traffic flow by providing timely and accurate information about the surrounding vehicles and the road environment [23], [24], allowing for more efficient and coordinated driving [22], [25]. Table 1 summarizes the benefits and challenges of V2V Communication in smart traffic systems.…”
Section: Results and Disccussionmentioning
confidence: 99%
“…Regarding Table 1, we identify Several benefits of using V2V communication in smart traffic systems such as Safety improvement [26] to prevent accidents and improve safety on the road, Efficiency improvement reduce congestion and improve efficiency on the road [25] where V2V communication can support the development of smart traffic systems, leading to improved efficiency and sustainability for transportation networks [27]. Traffic management improvement to improve safety on the road by alerting drivers to potential hazards and helping them to avoid accidents where V2V communication can allow vehicles to communicate with each other to coordinate merging and lane-changing activities, reducing the potential for accidents and improving traffic flow [28].…”
Section: The Benefit Of Using V2v Communication In Smart Traffic Systemmentioning
confidence: 99%